Traditional pediatric massage enhanced the skeletal muscle mass in OVA-exposed adolescent rats via regulating SCFAs-FFAR2-IGF-1/AKT pathway - Lin, Lin; Li, Siyuan; Liu, Que; Zhang, Xingxing; Xiong, Ying; Zhao, Shaoyun; Cao, Liyue; Gong, Jiaxuan; Liu, Yaping; Wu, Rong (Frontiers in Microbiology, 2025)
ObjectiveThis study aimed to investigate the potential relation between the retarded growth of skeletal muscle (SM) and dysbiosis of gut microbiota (GM) in children with asthma, and to explore the potential action mechanisms of traditional pediatric massage (TPM) from the perspective of regulating GM and short-chain fatty acids (SCFAs) production by using an adolescent rat model of asthma.MethodsMale Sprague-Dawley rats aged 3weeks were divided randomly into the 5 groups (n=6 7) of control, ovalbumin (OVA), OVA + TPM, OVA + methylprednisolone sodium succinate (MP) and OVA + SCFAs. Pulmonary function (PF) was detected by whole body plethysmograph, including enhanced pause and minute ventilation. Airway allergic inflammation (AAI) status was assessed by concentrations of OVA-specific immunoglobulin E in plasma, interleukin (IL)-4 and IL-1β in bronchoalveolar lavage fluid via ELISA assay. SM mass was assessed by using cross-sectional areas of diaphragm muscle and gastrocnemius via hematoxylin and eosin staining. GM and SCFAs production were detected by 16S rDNA sequencing and GC-MS, respectively. The protein and gene expressions of free fatty acid receptor 2 in SM were detected by using immunohistochemical staining and qRT-PCR, respectively. qRT-PCR was used to detect other relative gene expressions that were closely related with SM mass. The activity of insulin-like growth factor-1 (IGF-1)/protein kinase B (PKB/AKT) pathway in SM was detected by western blotting test.ResultsOVA exposure caused obvious AAI and poor PF in adolescent rats. OVA-exposed adolescent rats had a retarded growth of SM mass and inhibited activity of IGF-1/AKT pathway, which was related with GM dysbiosis, reduced SCFAs production and FFAR2 expressions in SM. TPM efficiently enhanced the SM mass, along with alleviating AAI and improving PF. TPM activated IGF-1/AKT pathway in SM, which was closely related with correcting GM dysbiosis, enhanced SCFAs production and FFAR2 expressions.ConclusionThe retarded growth of SM mass and inhibition of IGF-1/AKT pathway existed in OVA-exposed adolescent rats, which was related with GM dysbiosis, reduced SCFAs production and FFAR2 expressions in SM. TPM efficiently enhanced the SM mass, at least, partially via regulating GM, enhancing SCFAs production and activating FFAR2-IGF-1/AKT pathway.